Modernity, Magickal Cosmologies and Science: A New Cauldron for a New Age? - Green, Dave (Pomegranate, 2001)
Chaos magic, alternatively known as chaoism, is a radical, libertarian form of magick which appears to have the most overt scientific content in terms of cosmological understanding and magickal practice.